Increasing Role of Children in Family Purchase Decisions - Tripathi, Prashant; Sengupta, A. (Indian Journal of Marketing, 2011)
Children constitute an important target market segment and merit attention from a marketing perspective. The role that children play in making decisions concerning the entire family unit has prompted researchers to direct attention to the study of influence of children. The amount of influence exerted by children varies by product category and stage of the decision making process. For some products, they are active initiators, information seekers, and buyers; whereas, for other product categories, they influence purchases made by the parents. The purchasing act is governed by how they have been socialized to act as consumers. Family, peers, and media are key socializing agents for children wherein family-specific characteristics such as parental style, family’s Sex Role Orientation (SRO) and patterns of communication play key roles. More so, changes taking place in the socio-cultural environment in India (such as emergence of dual-career, single parent families) entail that dimensions of children’s influence in family purchase decision making be investigated in a specific context. Indian society vastly differs from the West in terms of family composition and structure, values, norms, and behavior, which affect the role that children play in purchase decision making in families. Hence, the aim of this paper is not only to explore the dimensions already investigated by previous researchers in India and Western Countries, but also to identify directions for future research.